"A thread connects all beads": Aligning global CSR strategy by hotel MNCs. (August 2022) - Ertuna, Bengi; Gu, Huimin; Yu, Larry
Abstract: Facing the global challenges of building a sustainable and equitable economy, hotel multinational corporations (MNCs) have leveraged their extensive global reach and business skills to guide local communities through the implementation of global corporate social responsibility (CSR) strategies. Our study explored the alignment of global CSR strategy by two hotel MNCs—Hilton Worldwide and Marriott International—using an institutional logics framework. Based on a two-country case study of China and Turkey, we uncover the mechanisms of implementation for alignment between MNC headquarters and affiliated hotels in host countries, where a plurality of logics interact and collide with the global CSR logic. We examine the dimensions of plurality of logics in the process of local implementation and unveil novel insights on logic reconciliation and activation to support systemic and transformative change through global CSR strategies of MNCs. We offer theoretical and practical implications and future research directions. Highlights: This study examined global integration of a CSR strategy in two hotel multinational corporations in China and Turkey. Novel mechanisms enabled alignment between headquarters and local hotels for CSR in the context of a plurality of institutional logics. Corporate logic dominated community and state logic in global strategic alignment of CSR. Local implementation tensions and facilitators were identified for supporting headquarters mechanisms. Hospitality logic facilitated strategic alignment, improving the potential of the MNCs to create awareness and impact.